Discovery of intermediate hosts for two species of blood flukes Cardicola orientalis and Cardicola forsteri (Trematoda: Aporocotylidae) infecting Pacific bluefin tuna in Japan. Issue 2 (April 2016) - Shirakashi, Sho; Tani, Kazuki; Ishimaru, Katsuya; Shin, Sang Phil; Honryo, Tomoki; Uchida, Hiro'omi; Ogawa, Kazuo
Abstract: Fish blood flukes (Aporocotylidae) are important pathogens of farmed finfish around the world. Among them, Cardicola spp. infecting farmed tuna are considered to be serious threats to tuna farming and have received tremendous attention. We conducted periodical samplings at a tuna farming site in Japan between January and May, 2015 to determine the life cycle of Cardicola spp. We collected over 4700 terebellid polychaetes from ropes, floats and frames of tuna culture cages and found nearly 400 infected worms. Sporocysts and cercariae found in Nicolea gracilibranchis were genetically identified as Cardicola orientalis by 28S and ITS2 ribosomal DNA sequences. This was the first discovery of the intermediate host for this parasite species. Infection prevalence and the abundance of N. gracilibranchis significantly varied between sampling points and the highest number of infected terebellids were collected from ropes. We also demonstrated morphologically and molecularly that asexual stages found in a single Amphitrite sp. (Terebellidae) and adult worms isolated from farmed juvenile tuna were Cardicola forsteri . This is the first report of C. forsteri in Pacific bluefin tuna (PBT) Thunnus orientalis in Japan. Our results demonstrated that all three species of Cardicola orientalis, C. forsteri and Cardicola opisthorchis exist in Japanese farmed PBTs and that they all use terebellid polychaetes as the intermediate hosts. Graphical abstract: Abstract : Highlights Blood fluke Cardicola forsteri was found in Pacific bluefin tuna and in Japan for the first time. A terebellid, Nicolea gracilibranchis, was identified as the intermediate host for C. orientalis Sporocysts of C. forsteri were found in a terebellid polychaete Amphitrite sp. Distribution and infection of intermediate host varied considerably between sampling points.